Autokorelasi Laba Dan Volatilitas Laba: Peningkat Audit Delay? - Rini Lestari; Pupung Purnamasari; Edi Sukarmanto (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to test the effect of earnings autocorrelation and earnings volatility on audit delay. In the process of the test, researchers used multiple regression analysis using a research sample of 105 manufacturing companies or 525 observations with the observation range of 2015 – 2019. The result, it showed that earnings autocorrelation had an effect on increasing audit delay. It is similar that the earnings correlation which also affects audit delays. The results of this study provide implications that auditors must be more careful in carrying out the audit process, especially in capturing earnings information from time to time. This is because earnings are the information that is often used by the users in assessing a company and used to manipulate earnings. For future research, it is suggested to use specialist industrial auditors as a coding variable in an effort to suppress the occurrence of long audit delays